Mucogingival Volumetric Changes After Root Coverage With Acellular Dermal Matrix: A Case Report. Issue 4 (1st November 2014) - Clozza, Emanuele; Suzuki, Takanori; Kye, Wayne; Horowitz, Robert A.; Engebretson, Steven P.
Abstract : Introduction: Monitoring mucogingival changes after treatment is of great interest for clinicians and researchers. Case Presentation: A 30‐year‐old non‐smoking male who exhibited multiple adjacent teeth with Miller Class I gingival recession in the esthetic zone underwent a root‐coverage procedure with an acellular dermal matrix graft. Dental stone casts of the maxilla were fabricated from impressions taken at baseline and 6 months after surgery. Subsequently, the entire surfaces of the casts were digitally captured with a three‐dimensional laser scanner. Virtual measurements were performed on superimposed casts to assess mucogingival changes during the 6‐month period. Complete resolution of gingival recessions was observed in all the treated sites, along with an overall increased thickness of mucosal tissues. Conclusion: Within the limitations of this case report, the proposed method may be promising for the evaluation of the outcome of root coverage and identifying biotype conversion.